Kinanthropometric comparison between young elite kayakers and canoeists - Alacid, F.; Marfell-Jones, M.; Muyor, J. M.; Martinez, I. (Collegium Antropologicum, 2015)
The aims of this study were to describe and compare kinanthropometric characteristics of elite young kayakers and canoeists and to compare their proportionality with Olympic paddlers. One hundred and twenty young elite sprint paddlers (66 kayakers and 58 canoeists), aged 13- and 14-years-old, were assessed using a battery of 32 anthropometric dimensions. Somatotypes, Phantom Z-scores and corrected girths were calculated. Comparison between kayakers and canoeists showed that kayakers had greater height, body weight, sitting height, arm span and upper body lengths, breadths and girths than canoeists. Higher proportional humerus breadth and arm girths were also found in kayakers. However, canoeists had higher Z-scores in femur breadth. Olympic paddlers had higher proportional dimensions in upper body girths, and biacromial breadth in both disciplines. Mean somatotypes of kayakers were best described as balanced mesomorphs, while canoeists were ecto-mesomorphs. Differences between kayak and canoe paddlers may be explained by the continual need for physical development in kayakers, in order to remain competitive, compared to the young canoeists` need to place much greater emphasis on the development of their technical ability. The data provided in this study could be used as a guideline for talent identifi cation in sprint canoeing and kayaking.